2020
DOI: 10.3389/fcimb.2020.00482
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Zonula occludens Toxin Found in the Genome of the Chilean Non-toxigenic Vibrio parahaemolyticus Strain PMC53.7

Abstract: Vibrio parahaemolyticus non-toxigenic strains are responsible for about 10% of acute gastroenteritis associated with this species, suggesting they harbor unique virulence factors. Zonula occludens toxin (Zot), firstly described in Vibrio cholerae, is a secreted toxin that increases intestinal permeability. Recently, we identified Zot-encoding genes in the genomes of highly cytotoxic Chilean V. parahaemolyticus strains, including the non-toxigenic clinical strain PMC53.7. To gain insights into a possible role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 55 publications
0
22
1
Order By: Relevance
“…Zot proteins have been associated with high cytotoxicity before (Pérez-Reytor et al, 2018), though this is not always the case. For instance, in Vibrio parahaemolyticus, "Zot" expression did not positively correlate with cytotoxicity, rather than with an actin disturbance on infected cells (Pérez-Reytor et al, 2020). Xf putative "Zot" proteins studied here appear not to correlate to cytotoxic effects.…”
Section: Fig S1)contrasting
confidence: 54%
“…Zot proteins have been associated with high cytotoxicity before (Pérez-Reytor et al, 2018), though this is not always the case. For instance, in Vibrio parahaemolyticus, "Zot" expression did not positively correlate with cytotoxicity, rather than with an actin disturbance on infected cells (Pérez-Reytor et al, 2020). Xf putative "Zot" proteins studied here appear not to correlate to cytotoxic effects.…”
Section: Fig S1)contrasting
confidence: 54%
“…Zot-type toxins have also been found in Vibrio parahaemolyticus and Vibrio vulnificus (Castillo et al, 2018a,b;Pérez-Reytor et al, 2018), both human pathogens. According to our recent studies, Zot would be associated with the actin cytoskeletal disturbances observed in Caco-2 cells after infection with a non-toxigenic strain of V. parahaemolyticus (Pérez-Reytor et al, 2020). On the other hand, it has been hypothesized that C. concisus disrupts gastrointestinal epithelium, driving a dysregulated immune response that results in chronic inflammation in the intestine (Mahendran et al, 2011;Zhang et al, 2014;O'Brien, 2017).…”
Section: Toxins That Damage the Tj: Zonula Occludens Toxinmentioning
confidence: 97%
“…Accessory cholera enterotoxin (Ace -VC1459) and zonula occludens toxin (Zot -VC1458) are accessory toxins that are both encoded near the CT genes on the CTXφ phage [136,137]. Zot leads to the disruption of the tight junctions between intestinal epithelial cells, an important structure in the intestinal permeability [138,139]. It is translocated and anchored in the outer membrane and has two functional domains.…”
Section: Other Secreted Moleculesmentioning
confidence: 99%
“…Thus, Zot does not employ a conventional secretion system for its release into the extracellular milieu. Regarding Ace, it leads to fluid secretion in rabbit ileal loop model by unbalancing calcium secretion and the secretion mechanism has not been determined yet [138].…”
Section: Other Secreted Moleculesmentioning
confidence: 99%